Special Area Plan (SAP) for Bandar Maharani, Johor Royal Town - Asmawi, M. Zainora; Mat Sundari, Mohamad Izzudin; Marzayee, Mazaruddin (Kulliyah of Architecture and Enviromental Design, International Islamic University Malaysia, 2019)
This project of Development Action Plan was carried out in a special royal town of Bandar Maharani, Johor. It is a historic town and the capital of Muar District, Johor. Though there are many potentials to be further enhanced, several issues need to be resolved for better environmental quality. The suggested development approach relates to its physical condition, taking advantage of Sungai Muar that lies in the middle of the town. Thus, the riverfront development is recommended with many improved elements of urban design to elevate the image of the urban heritage of Bandar Maharani. Among the key projects are water taxi, Sungai Bentayan open space and, Muar bridge gateway, and sky pedestrian.